An Empirical-informed Work Process Model for a Combined Approach of Agile, User-Centered Design, and Lean Startup - Zorzetti, Maximilian; Signoretti, Ingrid; Pereira, Eliana; Salerno, Larissa; Moralles, Cassiano; Machado, Michele; Bastos, Ricardo; Marczak, Sabrina (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
Organizations worldwide have been adopting software development methods that deviate from the standard Agile approach in order to overcome some of its failings—mostly by mixing Agile with other concepts. It has been reported that combining it with Lean Startup and User-Centered Design results in a very powerful development approach, and academic research has developed some high-level process models for it. However, in-depth, demonstrated work process models for this combined approach do not exist, which makes it hard for inexperienced professionals to start using it. We aim to present a process model that reflects how two industry teams that use the combined approach do their work. We performed a case study where we investigated their day-to-day work using daily observations, semi-structured interviews, and focus group sessions; and mapped a set of the activities, techniques, and work products that both teams use daily. We then had them visually represent their work process with the help of our mapping. The result was a software development process model that encompasses Agile, Lean Startup, and User-Centered Design concepts, which can be used as a starting point for those who want to adhere to such a development approach. We reflect on how the process model was conceived and how it could be used by other organizations.